THE ITALIAN GEOPOLITICAL CODE - Giovanbattista Varricchio (Сравнительная политика, 2018)
The aim of the research is to outline the main features of the Italian geopolitical code, that is to say the manner in which a given country orientates itself toward the world. Our argument is that – even though a secondary one - also Italy has shaped its own way to approach international relations. The work takes into consideration relevant events in Italian history and contemporary geopolitical orientation as reported into offi cial strategic documents. The fi nal result is the profi le of a country feeling its founding role of the main Western regional structures focusing mainly on regional interests. Nonetheless, its Italian friendly attitude toward outsider of Western bloc is a relevant peculiarity that brought Italy to be seen as a reliable partner by many global actors, even those opposing the West.